Biocatalysis with Unnatural Amino Acids: Enzymology Meets Xenobiology. Issue 33 (17th July 2017) - Agostini, Federica; Völler, Jan‐Stefan; Koksch, Beate; Acevedo‐Rocha, Carlos G.; Kubyshkin, Vladimir; Budisa, Nediljko
Abstract: The goal of xenobiology is to design biological systems endowed with unusual biochemical functions, whereas enzymology concerns the study of enzymes, the workhorses of biocatalysis. Biocatalysis employs enzymes and organisms to perform useful biotransformations in synthetic chemistry and biotechnology. During the past few years, the effects of incorporating noncanonical amino acids (ncAAs) into enzymes with potential applications in biocatalysis have been increasingly investigated. In this Review, we provide an overview of the effects of new chemical functionalities that have been introduced into proteins to improve various facets of enzymatic catalysis. We also discuss future research avenues that will complement unnatural mutagenesis with standard protein engineering to produce novel and versatile biocatalysts with applications in synthetic organic chemistry and biotechnology. Abstract : Unnatural design : The goal of xenobiology is the design of biological systems endowed with unusual biochemical units. For example, engineering the genetic code of enzymes to contain unnatural amino acids and cofactors can lead to unique properties that make the enzymes useful biocatalysts.